REVIEW OF THE EFFECTIVENESS OF IRRIGATION OPERATION MANAGEMENT SYSTEM (SMOI) TO SUPPORT THE MODERNIZATION OF IRRIGATION (Case Study: Bondoyudo Irrigation Area) - RAHMANDANI (NIM. 95015310), DADAN
The way of reporting and collecting irrigation data from all irrigation areas is done now using irrigation operation form in accordance with Decree of Minister of Public Works and Public Housing no. 15 / PRT / M / 2015 on guidelines for exploitation and maintenance of irrigation networks. Filling the blank is done manually in print stamps, especially by the irrigation operations actors at the level of mantri / interpreter and branch / observer. The distribution process of the already acquired stamps is done in stages to the other managers. This reporting process takes time, is more difficult to analyze and more difficult to trace, so decision-making on water sharing is also more difficult to address. Irrigation Operation Management System (SMOI) is an irrigation operating system developed by Irrigation Bureau. This system is a website-based irrigation operations application that prioritizes paperless concepts or replaces the role of paper in irrigation operations. This SMOI technology is designed to be able to perform the operational data of irrigation operation automatically by utilizing internet communication service network. This irrigation operation reporting application is expected to be able and effective enough to support irrigation operation so that irrigation water distribution can be done efficiently, and also support the concept of irrigation modernization especially operating system on the pillar of irrigation management. However, this SMOI technology has not been tested on field-scale applications especially in applications in cross-district irrigation areas. This study was conducted with the aim of analyzing the effectiveness of SMOI reporting in an effort to help speed up the reporting and communication process between water user farmers, field officers and government agencies dealing with irrigation in Bondoyudo Irrigation Area, East Java. This research was conducted by testing the application of irrigation operation management system (SMOI) in Bondoyudo Irrigation Area, then performed performance analysis and acceptance analysis at user level. The SMOI performance analysis focuses on the parameters of the accuracy of the calculation, the effectiveness of reporting and the accuracy of water delivery as the impact of the SMOI application. The acceptance of SMOI at user level is analyzed by TAM (Technology Acceptance Model) approach. The results of this study are expected to provide an overview of alternative irrigation management especially in the irrigation operations management system in Bondoyudo Irrigation Area. From the results of the research note that the process of calculation, retrieval and interconnection of data between blangko irrigation operations on the model SMOI quite accurate. The application of Irrigation Operation Management System (SMOI) in Bondoyudo Irrigated Publication can generally accelerate the irrigation operations reporting process compared to manual manpower, either at the planning stage (from 43 hours to 24.5 hours), the implementation (from 40 hours to 16 hours) reporting (from 45 hours to 27 hours). Based on the simulation results of water delivery accuracy, it is known that the water administration of SMOI can improve the accuracy of water supply to the prediction of the need for irrigation water by 36.5%. While the actual irrigation water requirement, the water supply of SMOI has not been seen to improve the accuracy of water supply, this is due to the evaluation of water requirement on the SMOI model 05-O bloom has not been taken into account based on actual climatological development. The results of the Delivery Perfomance Ratio (DPR) analysis show that SMOI water supply (3 daily) and 10 day water supply are categorized as excessive to actual irrigation water needs with an average value of House of Representatives of 2.01. The result of statistical analysis on the data of acceptance level of SMOI application in Bondoyudo Irrigation Area shows ease variable has influence on SMOI user attitude which gets support of 80,4% respondent agreed and has significance level 0,790. Benefit variables have a significant influence on SMOI user attitude which gets 92.2% of respondents answered agreed and has a significance level of 0.044. The results of the analysis show that irrigation management system (SMOI) from the side of the benefits is more influential for irrigation management use than in the case of convenience.